The Health Information Seeking Behavior of Punjabi Elders During the COVID-19 Pandemic in Canada - Amrit Thandi; Mohammad Z. I. Chowdhury; Nashit Chowdhury; Tanvir C. Turin (SAGE Publishing, 2024)
Health Information Seeking Behavior (HISB) refers to the behavior and strategies used to attain, clarify, or confirm health information. The uptake of health information depends on system-level and individual-level factors. The purpose of the present study is to understand the sources from which Punjabi elders obtain COVID-19 vaccine-related information and their information seeking behavior. A cross-sectional survey was conducted among 391 Punjabi elders aged 50+ years in the Greater Toronto Area (GTA), Ontario. The survey questions included the need for COVID-19 vaccine information, the type of information sought, sources of information, and barriers to seeking information. Descriptive analysis was conducted using frequencies and percentages, and logistic regression was performed to understand the associations between participants' sociodemographic characteristics and HISB. The results suggested that Punjabi elders are more likely to use informal sources and less likely to seek information from health professionals and government health and wellness websites. The results also suggested that most participants do not cross-check their information with other sources and are more likely to cross-check the information with family/friends, compared to credible care providers, across all demographics. Ultimately, there may be a need for stakeholders to collaborate to regulate the accuracy and type of health-information that is disseminated through media, and to tailor health communication to the health information seeking behavior of this population.